Cross‐Point Arrays with Low‐Power ITO‐HfO2 Resistive Memory Cells Integrated on Vertical III‐V Nanowires - Karl‐Magnus Persson; Mamidala Saketh Ram; Olli‐Pekka Kilpi; Mattias Borg; Lars‐Erik Wernersson (Advanced Electronic Materials, 2020)
Abstract Vertical nanowires with cointegrated metal‐oxide‐semiconductor field‐effect‐transistor (MOSFET) selectors and nonvolatile resistive random access memory (RRAM) cells represent a promising candidate for fast, energy‐efficient, cross‐point memory cells. This paper explores indium‐tin‐oxide‐hafnium‐dioxide RRAM cells integrated onto arrays of indium‐arsenide (InAs) vertical nanowires with a resulting area of 0.06 µm2 per cell. For low current operation, an improved switching uniformity over the intrinsic self‐compliant behavior is demonstrated when using an external InAs nanowire MOSFET selector in series. The memory cells show consistent switching voltages below ±1 V and a switching cycle endurance of 106 is demonstrated. The developed fabrication scheme is fully compatible with low‐ON‐resistance vertical III‐V nanowire MOSFET selectors, where operational compatibility with the initial high‐field filament forming is established. Due to the small footprint of a vertical implementation, high density integration is achievable, and with a measured programming energy for 50 ns pulses at 0.49 pJ, the technology promises fast and ultralow power cross‐point memory arrays.